Effects of heat and hyposalinity on the gene expression in Acropora pruinosa larvae - Chui, Apple Pui Yi; Wong, Yue Him; Sun, Jin; Chang, Taison Ka Tai; Qiu, Jian-Wen; Qian, Pei-Yuan; Ang, Put (Frontiers in Marine Science, 2023)
Climate change has resulted in elevated sea surface temperature as well as increased frequency of extreme weather events, e.g. cyclones and rainstorms, which could lead to reduced seawater salinity. While temperature effects on corals have been widely examined, the combined effects of both temperature and salinity on corals, especially their early stages, remain poorly known. This study aimed to examine how the larvae of Acropora pruinosa in a marginal coral habitat, Hong Kong, respond to high temperature (+5oC ambient, HT), low salinity (26 psu, LS), and the combined effects of both stressors (HTLS). Our results showed that the survivorship of coral larvae was not affected in all experimental treatments, with all larvae surviving through the 72-hour period of the experiment. Yet, larval settlement was compromised under all stress treatments. The settlement rates were 39.3%, 12%, and 0% for the elevated temperature, reduced salinity, and the combined treatment, respectively, which were all significantly lower than that under the control treatment (78%). Besides determining larval survival and settlement success, we used RNA-Seq technique to compare the gene expression patterns of these larvae under different experimental treatments to understand the underlying molecular mechanism of stress responses. We demonstrated that low salinity (LS) triggered responsive gene sets with functions in ATP production, protein translation, and receptor for neuroactive ligands. In addition, high temperature (HT) treatment also triggered MAPK and NF-kB signaling and apoptosis in these coral larvae. The combined stressor treatment (HTLS) acted synergistically, resulting in the up-regulation of intracellular transducers that could trigger the intrinsic apoptosis pathway. This may explain the total failure in larval settlement under HTLS that could further increase larval vulnerability in the natural environment. Our results provide new insights into the molecular responses of coral larvae and represent an essential first step in expanding our understanding of the mechanisms of tolerance that may be exhibited by coral larvae exposed to multiple stressors.